Medication use and microscopic colitis. Issue 9 (12th September 2021) - Sandler, Robert S.; Keku, Temitope O.; Woosley, John T.; Galanko, Joseph A.; Peery, Anne F.
Summary: Background: Microscopic colitis is an increasingly common cause of watery diarrhoea. Several classes of medications have been associated with microscopic colitis in prior studies. Aims: To determine the association between the use of previously implicated medications and microscopic colitis. Methods: This was a case‐control study of patients referred for elective, outpatient colonoscopy for diarrhoea. Patients were excluded for inflammatory bowel disease, C difficile, or other infectious diarrhoea. Colon biopsies were reviewed by the study pathologist and patients were classified as microscopic colitis cases or non‐microscopic colitis controls. Results: The study population included 110 microscopic colitis cases and 252 controls. The cases were older, better educated and more likely to be female. Cases reported a greater number of loose, watery, or liquid stools, nocturnal stools, more urgency and weight loss compared to controls. There was no association with proton pump inhibitors (PPIs), adjusted OR (aOR) 0.66, 95% CI 0.38‐1.13 or nonsteroidal anti‐inflammatory drugs, aOR 0.68, 95% CI 0.40‐1.17. Cholecystectomy was less common in cases, aOR 0.33, 95% CI 0.17‐0.64, but microscopic colitis cases had more frequent bowel movements following cholecystectomy. Conclusion: Compared to similar patients with diarrhoea, cases with microscopic colitis were not more likely to have taken previously implicated medications. They had more diarrhoea following cholecystectomy, suggesting that bile may play a role in symptoms or aetiology. We conclude that the appropriate choice of controls is crucial to understanding risk factors for microscopic colitis. Abstract : Odds ratio (95% confidence interval) adjusted for age, sex and education for medications taken in the year prior to diagnosis and microscopic colitis.